Shari’ah Governance Disclosure: A Key to Financial Success through Governance Mechanisms in Islamic Banks - Fahru Azwa Mohd Zain; Wan Amalina Wan Abdullah (Asian Journal of Business and Accounting, 2024)
Manuscript type: Research paper Research aims: This study aims to explore the relationship between governance mechanisms, Shari’ah governance disclosure, and performance in Islamic banks operating in Southeast Asia and the Gulf Cooperation Council. Design/Methodology/Approach: Using a Structural Equation Model, the research establishes the Shari’ah governance disclosure index based on the standards set by the Accounting and Auditing Organization for Islamic Financial Institutions, the Islamic Financial Services Board, and prior studies. Research findings: The results reveal a significant positive impact between governance mechanisms and performance in Islamic banks. Furthermore, Shari’ah governance disclosures partially mediate between governance mechanisms and the performance of Islamic banks. Theoretical contribution/Originality: This study contributes to the literature by shedding light on the dynamics of Shari’ah governance disclosure, governance mechanisms, and performance in Islamic banking, thereby offering valuable insights for both academia and practitioners. Practitioner/Policy implication: The findings suggest that enhancing governance mechanisms is crucial for Islamic banks to improve their performance. Regulators can leverage these insights to strengthen Corporate Governance and the effectiveness of Shari’ah Supervisory Boards, which can lead to increased financial stability and stakeholder trust. Research limitation: One limitation of this study is its focus on Islamic banks in Southeast Asia and the Gulf Cooperation Council, which may restrict the generalisability of the findings.